2019
DOI: 10.1007/s00520-019-05098-0
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a novel exercise prehabilitation programme in patients scheduled for elective colorectal surgery: a feasibility randomised controlled trial

Abstract: Background and objectives To investigate the feasibility of delivering a functional exercise-based prehabilitation intervention and its effects on postoperative length of hospital stay, preoperative physical functioning and health-related quality of life in elective colorectal surgery. Materials and methods In this randomised controlled feasibility trial, 22 elective colorectal surgery patients were randomly assigned to exercise prehabilitation (n = 11) or standard care (n = 11). Feasibility of delivering the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
88
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(99 citation statements)
references
References 28 publications
(24 reference statements)
2
88
2
Order By: Relevance
“…However, although the sample size was limited, once the study has been accepted by the patients, the overall acceptability of the intervention was good, with 85% of them having completed the study (15% did not due to technical problems related to the bracelet or withdrawal of consent). As described previously in another colorectal surgery cohort, patient engagement represented a major obstacle for the success of a prospective study assessing physical activity [43]. The present study should be considered as pilot and has highlighted the logistical issues and the challenges in recruiting patients to assess their physical activity.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…However, although the sample size was limited, once the study has been accepted by the patients, the overall acceptability of the intervention was good, with 85% of them having completed the study (15% did not due to technical problems related to the bracelet or withdrawal of consent). As described previously in another colorectal surgery cohort, patient engagement represented a major obstacle for the success of a prospective study assessing physical activity [43]. The present study should be considered as pilot and has highlighted the logistical issues and the challenges in recruiting patients to assess their physical activity.…”
Section: Discussionmentioning
confidence: 81%
“…Feasibility of a prospective study is based on recruitment and compliance to the intervention [43]. In the present study, the patient recruitment rate was low (15%), as a large majority refused to participate due to lack of interest.…”
Section: Discussionmentioning
confidence: 93%
“…This demonstrates that out of the eligible patients, most were willing to undertake an exercise program before their major surgery. Other comparable pilot trials demonstrated a less favourable result, with some reporting a recruitment rate of 20% and 62% [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The stair climbing test (SCT) and five times sit to stand (FTSTS) were assessed in the same small study as the TUG, with the SCT showing a favourable improvement (mean difference of −0.32 s compared to the control group 0.12 sec) whereas no pattern of improvement was reported in the FTSTS (15). Another study showed a 19% improvement in 10 metre walk test (10MWT) in the prehabilitation group, however this was not assessed against a control group for comparison (10).…”
Section: Functional Outcomes and Cardiopulmonary Fitnessmentioning
confidence: 99%
“…Although individual programs have been shown to increase preoperative fitness (9), heterogeneity in study designs has limited the synthesis of evidence regarding effects on postoperative outcomes in those undergoing abdominal surgery for cancer (6,7). Several randomised controlled trials (RCTs) (8,(10)(11)(12)(13)(14)(15) have been published since the last systematic review in this field of research (7). This systematic review set out to evaluate and synthesise the evidence examining the effect of prehabilitation on postoperative outcomes in patients undergoing abdominal cancer surgery.…”
Section: Introductionmentioning
confidence: 99%